POTENSI USAHATANI MELATI RATOH EBUH SEBAGAI KOMODITI UNGGULAN DAERAH DI JAWA TIMUR - Tamami, Novi Diana Badrut (9-772301-994005, 2013)
Bangkalanâs jasmine is popularÂ  as âRatoh EbuhÂ  jasmine had been promoted as prime commodity and most produced in Burneh district with 50 acres harvest area and the productivity is 0,34 kg/m2. The increasing of population in Indonesia, become a great market of jasmine commodity, beside that, an export opportunity is also opened for this flower. But the farmer of jasmine cannot supply the market need. The aim of this study is to show the cash flow analysis and financial feasibility study of âRatoh Ebuhâ jasmineâs farm enterprises to influence the farmer to invest in this farming enterprises, that able to rise the benefit of the jasmine farmers. Based on research, the total cost of jasmine farm enterprise is Rp.173.705.525 per acre for 4 years . The total net benefit that able to reach by the farmer is Rp. 241.207.140. This farm enterprise need 1 year, 2 months and 2 weeks to returns the total of capitals. Based on the evaluation of the feasibility level, the project is feasible to operated. The NPV value is Rp. 155.075.617 with the value of OCC is 12%. The IRR value is 77% and the ratio of net B/C is 4,4.